Preparation of Polish Accession into Euro Zone in the Time of Financial Crisis - Kundera, Jarosław (Przygotowanie Polski do członkostwa w strefie euro w czasach kryzysu finansowego, 2009)
Taking into consideration economic arguments the introduction of euro still brings more advantages then disadvantages for Polish economy. The impulse for additional growth from euro adoption would come mainly from: the intensification of trade with the EU member countries, the increase of competition on Polish market, the elimination of risk of rate of exchange, the increase of attractiveness of Polish market for international direct investment and new opportunities for Polish economic agents to finance their activities on European Single Market. The economic costs may occur in the long run which is related to the fact that economic structure of Polish economy is not perfectly similar to the EU core states and there is low flexibility of wages in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 34-49
Keywords: euro; convergence criteria; inflation; budgetary deficit; public debt